An empirical investigation of automation technology as material waste mitigation measure at Johor construction sites - Abkar, Mahdi Mohammed Abdullah; Yunus, Riduan; Al-Shameri, Ahmed Saleh Ahmed Saif; Harouache, Ahmed; Gamil, Yaser (Frontiers in Built Environment, 2023)
Automation technology in the construction industry is the use of advanced tools, devices, and processes that reduce manual labor and enhance efficiency in various construction activities. Automation technology can minimize waste, optimize resource utilization, and reduce the environmental impact of construction processes. This study aims to examine the relationship between automation technology adoptions (ATAs) utilizing reduce, reuse, and recycle (3R), building information modeling (BIM), industrialized building systems (IBSs), green building index (GBI), and Internet of Things (IoT) practices toward construction site performance (CSP) to measure their influences on material waste mitigation measures at Johor construction sites. To achieve these goals, five hypotheses were developed to explore the association between ATA and CSP. Data were gathered utilizing an online survey. The participants were contractors and expert practitioners in the Johor construction industry, including architects, project managers, and academicians/researchers. A total of 257 valid responses were used to investigate the assumptions. The partial least squares structural equation modeling (PLS-SEM) procedure was used. The findings revealed that ATA utilizing 3R, BIM, IBS, GBI, and IoT as material mitigation measures positively enhances CSP.